Maize pollen mutation by low energy ion beams - Yongliang, Li (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
A mensuration method to evaluate pollen viability with low energy in maize was established in this study. Several challenges experienced during ion implantation pollen mutation research were overcome, including pollen loss from run-off during vacuum pumping, and high pollen mortality rates. The data showed that a half lethal dose of 1×1014 N+ cm-2 at low-energy 30 keV was most effective for treating maize pollen. Three elite inbred lines were treated in this study. Some mutants such as white anther color, red seed capsules, lethal seed and albino seedling mutants were observed in the M0 and M1 populations. The results demonstrated that the pollen treatment with low-energy ion beam was an effectual method in maize mutant breeding.